2017
DOI: 10.1038/s41598-017-14171-9
|View full text |Cite
|
Sign up to set email alerts
|

Sustained accuracy improvement in intraocular lens power calculation with the application of quality control circle

Abstract: Accurate intraocular lens (IOL) power calculation is always a challenge in ophthalmology, and unoptimized process may lead to inaccurate refractive outcomes. Quality control circle (QCC) has shown its success in many fields as a process management tool. However, its efficacy in ophthalmology remains unclear. Here we utilized the QCC method to optimize the process and evaluate its efficacy in improving the accuracy of IOL power calculation. After the QCC application, the percentage of eyes with achieved refract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…of the QCC project discussed multiple possible strategies for each major problem in the form of a brainstorm. Subsequently, the strategies were graded by all members of the project based on a 5-point system, considering from three aspects included feasibility, economy and circle ability (13). Those strategies that received a higher score for each major issue were selected.…”
Section: Baseline Status Evaluation and Major Reasons Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…of the QCC project discussed multiple possible strategies for each major problem in the form of a brainstorm. Subsequently, the strategies were graded by all members of the project based on a 5-point system, considering from three aspects included feasibility, economy and circle ability (13). Those strategies that received a higher score for each major issue were selected.…”
Section: Baseline Status Evaluation and Major Reasons Analysismentioning
confidence: 99%
“…Since 2001, QCC was introduced to medical institutions in China in order to improve the quality of medical services by strengthening medical workers' awareness for discovering and solving medical problems, it is widely used in many aspects of improving medical quality. For example to reduce blood culture contamination rates for department of clinical laboratory (12), improve the intraocular lens power calculation for ophthalmology department (13), improve the hand hygiene compliance (14), reduce the incidence of catheter-associated urinary tract infection for department of nosocomial infection control (15), and so on. However, to our knowledge, no studies have been reported on QCC reducing carbapenem resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Countermeasure formulation and implementation: (1) Update painkilling concept to nurses and increase their sense of responsibility significantly. Enhance learning and training of pain knowledge, further increasing their abilities in pain assessment, education, and handling, as well as change their original wrong concepts and attitudes of pain treatment [10].…”
Section: Analysis Of Current Situationsmentioning
confidence: 99%
“…Pain nursing plays a unique role in pain diagnosis and treatment [1]. Along with the continuous development of medical nursing in recent years, employing pain nursing in clinics has attracted considerable interest [2].…”
Section: Introductionmentioning
confidence: 99%
“…As part of total quality management, it has become an important medical quality management activity in many hospitals. [ 1 ] The achievement of QCC refers to various issues such as new business, new processes, new services or development of new products, breakthroughs in the status quo, and creation of attractive qualities. Some studies indicated the role of QCC in medical improvement and highlighted the success of its application in medical care and hospital management.…”
Section: Introductionmentioning
confidence: 99%